Scientific Communication During the Current Pandemic and Some Considerations on Expressions of Concern - Retractions [la Comunicación Científica Durante la Actual Pandemia y Algunas Consideraciones Sobre Expresiones de Preocupación - Retractaciones] - Vanegas-Lopez, J (Sociedad Medica de Santiago, 2020)
[No abstract available]